Specification for titanium and titanium-alloy welding electrodes and rods (American Welding Society, 2013)
This specification prescribes the requirements for the classification of over 30 titanium and titanium-alloy welding electrodes and rods. Classification is based on the chemical composition of the electrode. Major topics include general requirements, testing, packaging, and application guidelines. This specification makes use of both U.S. Customary Units and the International System of Units (SI). Since these are not equivalent, each system must be used independently of the other. This specification adopts the requirements of ISO 24034 and incorporates the provisions of earlier versions of A5.16/A5.16M, allowing for classifications under both specifications.
"AWS A5.16/A5.16M:2013."
"Approved by the American National Standards Institute, February 19, 2013."
"Supersedes AWS A5.16/A5.16M:2007."
Keywords: Oxyacetylene welding and cutting -- Specifications -- United States.; Filler metal -- Specifications -- United States.; United States.; elektronické knihy; electronic books